Optimalisasi Keuntungan dan Pemanfaatan Waktu Kerja Pada UMKM Kapsul Herbal Sekar Utami Toga Tangerang Selatan Banten Menggunakan Program Linear Metode Simplek Dengan Aplikasi Komputer POM QM - Adi, Yakobus Saktono (Dinasti Research, 2025)
The purpose of this study is to find the optimum production and working time utilization solution for gaining optimum profit through the production of herbal capsule at Micro, Small, Medium Enteprise (MSME) Sekar Utami Toga South Tangerang Banten using simplex method linear programming. This study uses a quantitative approach. The data collection technique used in this study was obtained through primary and secondary data collection from the interview with the owner and 2 employees to know the company’s history, product selling prices, sales report, the number of raw materials used per-product, raw material used in 2024 and raw materials stocks for production in 2025. The sampling technique used was non-random sampling with purposive sampling technique where 8 herbal medicine capsules were chosen based on the observation findings. The data analysis used is simplex method linear programming using POM-QM computer application program and Excel. The result shows the maximum production of the 8 herbal capsules can increase company’s optimum profit up to Rp. 55.496.590,50 with the total working time increase up to 1 hour 43 minutes/working day.